Computational acoustics theory and implementation - Bergman, David R. (Wiley series in acoustics, noise and vibration, 2018)
Covers the theory and practice of innovative new approaches to modelling acoustic propagation There are as many types of acoustic phenomena as there are media, from longitudinal pressure waves in a fluid to S and P waves isseismology